2009
DOI: 10.1128/aem.00609-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of a NovelXylella fastidiosaSubspecies Found in the Southwestern United States

Abstract: Xylella fastidiosa, the causal agent of several scorch diseases, is associated with leaf scorch symptoms in Chitalpa tashkentensis, a common ornamental landscape plant used throughout the southwestern United States. For a number of years, many chitalpa trees in southern New Mexico and Arizona exhibited leaf scorch symptoms, and the results from a regional survey show that chitalpa trees from New Mexico, Arizona, and California are frequently infected with X. fastidiosa. Phylogenetic analysis of multiple loci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 39 publications
0
49
0
8
Order By: Relevance
“…Although four subspecies are commonly recognized within X. fastidiosa, there are reports of variants that may belong to two other subspecies, though these have yet to be well described (Su et al 2012;Randall et al 2009). Although various approaches have been used to study X. fastidiosa genetic diversity, multi-locus sequence typing (MLST) has provided the most valuable insights into the evolutionary history of this pathogen .…”
Section: Comparative Sequence Analysismentioning
confidence: 99%
“…Although four subspecies are commonly recognized within X. fastidiosa, there are reports of variants that may belong to two other subspecies, though these have yet to be well described (Su et al 2012;Randall et al 2009). Although various approaches have been used to study X. fastidiosa genetic diversity, multi-locus sequence typing (MLST) has provided the most valuable insights into the evolutionary history of this pathogen .…”
Section: Comparative Sequence Analysismentioning
confidence: 99%
“…Though isolates from these subspecies are genetically too similar for further taxonomic classification, studies on the biological traits of isolates from the same subspecies have indicated differences in infectivity (2,3,29,37,45,51). Because of this, efforts to further characterize the diversity seen among X. fastidiosa isolates within the proposed subspecies are ongoing (91).Diverse molecular techniques have been applied to genetically characterize X. fastidiosa isolates, including restriction fragment length polymorphism (RFLP) (10), random amplification of polymorphic DNA (RAPD) (3,12,32,65), microsatellite/simple sequence repeat (SSR) analysis (2,35,48,67), and 16S-23S rRNA internal transcribed spacer (ITS) sequencing (32,54,56,67). Results from strain typing, phylogenetic analyses, and other data comparisons in the aforementioned studies have shown broad host-based genetic differences between strains; however, phylogenetic results on differentiation of strains from within the same X. fastidiosa subspecies and those isolated from the same host plant species are still inconclusive.…”
mentioning
confidence: 99%
“…Diverse molecular techniques have been applied to genetically characterize X. fastidiosa isolates, including restriction fragment length polymorphism (RFLP) (10), random amplification of polymorphic DNA (RAPD) (3,12,32,65), microsatellite/simple sequence repeat (SSR) analysis (2,35,48,67), and 16S-23S rRNA internal transcribed spacer (ITS) sequencing (32,54,56,67). Results from strain typing, phylogenetic analyses, and other data comparisons in the aforementioned studies have shown broad host-based genetic differences between strains; however, phylogenetic results on differentiation of strains from within the same X. fastidiosa subspecies and those isolated from the same host plant species are still inconclusive.…”
mentioning
confidence: 99%
“…First, the cause may be the acquisition of asymptomatic nursery tree material infected with X. fastidiosa from the central region and subsequent introduction onto the northwestern region for establishment of new coffee plantations. Another explanation is that these two geographical populations shared migrants from a common inoculum reservoir selective to host-specific X. fastidiosa genotypes, and that did not occur in other regions (Hernandez-Martinez et al 2007;Purcell and Saunders 1999;Randall et al 2009). Finally, it is plausible that the high levels of X. fastidiosa migration detected between central and northwestern SĂŁo Paulo State populations may be a consequence of migrants exchanged with a third population not sampled in our study.…”
Section: Discussionmentioning
confidence: 99%